(untitled) (Journal of Engineering, 2012)
This paper describes a practical study on the impact of learning’s partners, Bluetooth Broadcasting system, interactive board, Real – time response system, notepad, free internet access, computer based examination, and interaction classroom, etc, had on undergraduate student performance, achievement and involving with lectures. The goal of this study is to test the hypothesis that the use of such learning techniques, tools, and strategies to improve student learning especially among the poorest performing students. Also, it gives some kind of practical comparison between the traditional way and interactive way of learning in terms of lectures time, number of tests, types of tests, student’s scores, and student’s involving with lectures. This paper studies the effect of using relatively new technology appearing in classroom today which is real time response system (voting system), that serves as real – time windows into each students understand of concepts. These devices can provide a foundation decision making based on data at scale never before possible as well as increasing students learning and engagement with each other as well with the lecturer, also, another new technology the "Bluetooth broadcasting system" is applied which is one of the moderate technique towards M- learning, this tool is used to transfer audio, video, text, notes, etc to the mobile of the students as well as laptop. The computer based examination, interactive board, and notepad as well as free wire and wireless internet access are used to close the digital divide and increasing technology literacy in all students which was one of the challenges, additional challenges include “social loafing,” characterized by students who work less diligently than they otherwise might, or who become frustrated by course material or technology and thus less engaged. Finally the other colleague’s resistance to the use of technology in learning and its effect on students learning is discussed based on practical situations.